4CPS-285 Multidisciplinary oral therapy outpatient clinic: an Italian single centre experience. (14th March 2021) - Fazzina, G; Bellero, M; Marino, D; Terzolo, S; Sperti, E; Zichi, C; Codegone, F; Paratore, C; Ciriolo, G; Di Maio, M; Gasco, A
Abstract : Background and importance: The increasing use of oral anticancer drugs (OAD) has led to new challenges for clinicians. The traditional therapeutic horizon has changed, but data about new cancer care models are still scarce. Multidisciplinary management involving three distinct figures (medical oncologist, hospital pharmacist and nurse) could improve compliance and treatment (trt) safety. Aim and objectives: The aim of this analysis was to describe the oral therapy outpatient clinic (OOC), a multidisciplinary project performed at our oncology unit. A multidisciplinary approach focused on prescription, therapeutic education, drug interaction, monitoring and follow-up, to improve patients awareness, addressing medication safety, trt adherence and adverse events (AEs) management. Material and methods: OOC was limited to patients with gastrointestinal (GI) tumours. Three professional figures (medical oncologist, hospital pharmacist and nurse) performed joint visits (each with specific tasks), with a schedule based on patient and trt characteristics. Results: Between March 2019 and April 2020, 359 visits were performed in 49 patients: 23 (46.9%) were men, 100% were ECOG PS 0–1 and median age was 66 years (range 34–80). Overall, 22 patients (44.9%) received adjuvant trt and 27 patients (55.1%) trt for advanced disease. 8 patients (16.2%) had received ≥2 previous trt lines. 32 patients (65.3%) had colorectal cancer, 5 patients (10.2%) had hepatocarcinoma, 7 patients (14.3%) had biliary tract carcinoma and 5 patients (10.2%) had other types of GI tumours. Capecitabine was the most frequent CT (73.5%). 6 patients (12.2%) received trifluridine/tipiracil, 5 patients (10.2%) sorafenib and 2 patients (4.1%) regorafenib. Only 19 patients (38.8%) started a full dose trt (33.3% among patients aged >70 years vs 41.9% in patients aged ≤70 years). 29 patients (59.2%) had to delay ≥1 trt cycle (61.1% aged >70 years vs 58.1% aged ≤70 years). 27 patients (55.1%) required ≥1 dose modification due to toxicity, including haematological, cutaneous and GI AEs (50.0% >70 years vs 58.1% ≤70 years). 35 patients (71.4%) took ≥4 concomitant drugs: ≥1 drug interaction was found in 32 patients, requiring trt adjustment in 29 patients. Conclusion and relevance: OAD require comprehensive and integrated patients management. Multidisciplinary simultaneous visits involving an oncologist, pharmacist and nurse could optimise trt management, safety and outcomes. This innovative cancer care model could improve drug awareness of drug consumption and patient education to promptly recognise and manage AEs. References and/or acknowledgements: Conflict of interest: No conflict of interest